Correlation of Clinical Outcomes with β-Glucan Levels in Patients with Invasive Candidiasis - Sims, Charles R. (American Society for Microbiology, 2012)
The correlation of β-glucan (BG) levels with clinical outcomes in invasive candidiasis (IC) remains unknown. Patients with proven IC were followed prospectively from diagnosis to outcome with twice-weekly serum BG sampling. Correlation of BG with clinical outcome was assessed in each patient. BG levels tend to decrease in successfully treated patients and increase in treatment failures. BG levels may be useful as surrogates for outcome evaluation of IC.